Psychological and Contractual Scenario for a Successful Tender - Eilenberg, Ian M. (Revista Ingeniería de Construcción, 2000)
There is now a body of knowledge that proposes that the quantum of contract disputes suffered by a project can be related to the both the system of tendering adopted, and the documentation (both quantity and quality) prepared for use in the project construction process. Research by the author also demonstrated that on top of the purely physical nature of the tender system adopted and the documentation provided, a failure of the parties to the contract (even as early as the tender period) to have adequate communications in all its forms, will contribute to the likelihood of disputes occurring at some stage through-out the project. This problem may go much deeper than simply a failure to communicate between two people. It may reflect serious psychological problems between the parties that will need to be addressed if disputes, caused by inappropriate tender systems and contract documentation are to be avoided and to permit a successful project to be undertaken.